Air Pollution Control Devices: A Comparative Study. - SINGH, MAKHAN; KAUR, DALJEET; SINGH, CHARANJIT (Asian Journal of Chemistry, 2010)
To check the growing menace of air pollution, a general awareness among the masses about the pollution aspects of the society has become utmost essential in modem times. We, therefore, have ventured to correlate all the aspects of sources of air pollution, structure and composition of atmosphere, sources of pollutants, their transformation, transport and effects on all animates and inanimates and air pollution control devices commonly used in modem industries. The industries chosen are SmithKline, Beecham (H.M.M.) Nabha, Milk Food India Ltd., Bahadurgarh, Patiala, Rasan Detergents, Bahadurgarh, Patiala, Punjab, India.